2010
DOI: 10.1007/s00508-010-1373-6
|View full text |Cite
|
Sign up to set email alerts
|

Current standards in the treatment of metastatic breast cancer with focus on Lapatinib: a review by a Central European Consensus Panel

Abstract: In breast cancer, early detection as well as new developments in therapeutic options has resulted in less patients presenting with metastatic disease. However, about one-third of women with early stage breast cancer will eventually develop metastatic disease. Furthermore, approximately 20-30% of patients with breast cancer have tumors that overexpress human epidermal growth factor receptor (HER-2), which is associated with an aggressive tumor phenotype and poor prognosis. The identification of the HER-2 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…HER-2 (human epidermal growth factor receptor 2) status is an important clinical marker for treatment, with about 30% of patients presenting increased levels of HER-2expression[33]. Patients that are HER-2 positive are considered candidates for treatment with HER-2 inhibitors, including trastuzumab (Herceptin, Genentech) and lapatinib (Tykerb/Tyverb GSK)[36]. Recently, new small molecule-based therapeutics targeting EGFR, including erlotinib (Tarceva, OSI Pharmaceuticals), have proven useful in other cancers with upregulation of EGFR signaling[37].…”
Section: Invadopodia and Pdgfrα Are Necessary For Metastasis And Implmentioning
confidence: 99%
“…HER-2 (human epidermal growth factor receptor 2) status is an important clinical marker for treatment, with about 30% of patients presenting increased levels of HER-2expression[33]. Patients that are HER-2 positive are considered candidates for treatment with HER-2 inhibitors, including trastuzumab (Herceptin, Genentech) and lapatinib (Tykerb/Tyverb GSK)[36]. Recently, new small molecule-based therapeutics targeting EGFR, including erlotinib (Tarceva, OSI Pharmaceuticals), have proven useful in other cancers with upregulation of EGFR signaling[37].…”
Section: Invadopodia and Pdgfrα Are Necessary For Metastasis And Implmentioning
confidence: 99%
“…Both trastuzumab, and lapatinib, have been approved by the FDA and the European Medicines Agency (EMEA) for BC treatment. Lapatinib (Tykerb/Tyverb) was FDA approved in 2007 for use in combination with capecitabine for the treatment of HER2-positive (HER2+) advanced or MBC in patients who had received previous treatment (including anthracycline, taxane and trastuzumab containing regimens) and in 2010 it was approved in combination with letrozole for postmenopausal women with hormonal receptor positive and HER2+ MBC 8,10,[17][18][19][20] . TKIs are cheaper and easier to produce than monoclonal antibodies 21 .…”
Section: The Her Family and Its Blockadementioning
confidence: 99%
“…Overexpression of HER-2 has been shown to be associated with an aggressive tumor phenotype and poor prognosis [101]. Trastuzumab (Herceptin) is a recombinant, humanized, monoclonal antibody that binds to the extracellular domain of the HER-2 protein.…”
Section: Antibody Therapymentioning
confidence: 99%
“…Trastuzumab (Herceptin) is a recombinant, humanized, monoclonal antibody that binds to the extracellular domain of the HER-2 protein. Trastuzumab has been approved by the FDA and clinical trials have shown its efficacy for metastatic and early-stage HER-2-positive breast cancer [101,102].…”
Section: Antibody Therapymentioning
confidence: 99%